LEVEL OF FAILURE RISK BASED ON LAND TYPOLOGY OF PARTICIPANTS OF RICE FARM INSURANCE PROGRAMS IN SOUTH SUMATERA - Dwi Kuncorojati; M. Yamin; Yunita Yunita (JSEP (Journal of Social and Agricultural Economics), 2021)
Risk level in South Sumatra differs based on the land typology in which Buay Madang Timur District in East OKU Regency with typical irrigation rice field typology has different risk level compared to Banyuasin Regency with its tidal land typology. This research was aimed to find out risk failure in two land typologies nad losses due to its risk. The calculation of Z score was used to calculate risk level using cross data section in year 2019. Data were collected from each district with 120 AUTP farmer participants consisted of 60 samples of tidal land typology and 60 technical irrigation. Which 60 samples consisted of 52 unclaimed farmers and 8 claimed farmers. Based Z score calculation of crop failure risk, it was resulted that technical irrigation land typology in OKU Regency had 44% risk level due to rat and planthopper attack, compared to 49% tidal land typology in Banyuasin Regency that caused rat attack. Risk impact due to crop failure was then calculated using the Value at Risk (Var) method. Results showed that crop failure losses in East OKU Regency were equal to Rp. 11.304.361,- for each planting season while in Banyuasin Regency it was Rp. 12.445.273,-. Thus, the impact of crop failure risk in tidal land typology was greater than technical irrigation.